Implementasi Program Magrib Mengaji dalam Membentuk Karakter Religius Anak di Desa Tambangan Jae Kecamatan Tambangan - Abul Haris Hasibuan; Muhammar Fuadi; Desi Safitri; Siti Marwah; Nur Aliyah; Cindy Aulia; Hasnawiyah; Sri Wahyuni; Alwi Bisri; Ainun Mardia Harahap (Indo Publishing, 2025)
The cultivation of religious character from an early age plays a crucial role in faith-based education. The Magrib Mengaji program serves as a strategic initiative to instill Islamic values while strengthening children’s Qur’anic literacy. This study seeks to describe the implementation of the Magrib Mengaji program in Tambangan Jae Village and examine its contribution to the development of children’s religious character. Using a qualitative approach, data were gathered through participatory observation, in-depth interviews, and documentation. The results reveal that the program is conducted regularly with strong support from parents, Qur’an teachers, and community leaders. Children demonstrated notable progress in Qur’an reading, memorization of prayers, and daily worship practices, along with the development of discipline, responsibility, and cooperation. Despite challenges such as limited teaching staff and the influence of digital devices, the Magrib Mengaji program has proven effective in nurturing the religious character of young generations. Sustained efforts through better facilities, teacher training, and parental involvement are essential to ensure the continuity and impact of this program in shaping a devout and well-mannered generation.